The agile city : - Russell, James S (Island Press, 2011)
The Agile City highlights tactics that create multiplier effects, which means that ecologically driven change can shore-up economic opportunity, can make more productive workplaces, and can help revive neglected communities. Being able to look at multiple effects and multiple benefits of political choices and private investments is essential to assuring wealth and well-being in the future. Green, Russell writes, grows the future.